What Causes Special Educators to Become Burned Out? - Bong-Theisen, Michelle Ann (My University, 2012)
This research study was designed to determine that causes that lead burn out amongst special education teachers. The study was a study that was compared to a study done in 1987. The researcher administered a survey to 27 participants in an elementary school, middle school, and high school. The study looked at four reasons that may cause burn out amongst special education teachers. 1. How many years of teaching experience do you have as a Special Education teacher? 2. How many years teaching experience do you have in working with students with learning disabilities, emotional and or behavioral disabilities, or cognitive disabilities? 3. What other degrees or certification do you currently hold? 4. Why did you choose to enter the special education field as a teacher? The findings in the 2012 study compared to the 1897 study showed that based on the results of the study and surveys, I have found the problem of burn out among special educators still occurs much too often. Many of the same factors still cause burn out as my survey answers still showed to be very similar. There is still too much paperwork overload involved in the job, too many students on one caseload for special education teachers, and there is lack of time for special education teachers to complete their job duties. There are positive results that did show true about special educators feeling more support amongst colleges. This is due to weekly meetings, team teaching or co-teaching, professional development, and all around more collaboration.
Keywords: special education teachers; burn out